Are the cooperatives in more favourable of having woman in their board of directors than other entities?ES? - Esteban Salvador, Mª Luisa (REVESCO. Revista de Estudios Cooperativos, 2013)
This paper analyzes which companies have more women on their board of directors in the moment previous to the publication of measures and recommendations about the female presence on the boards of directors of the Spanish big companies, including cooperatives. At the same time the study puts in relation the gender on boards with the return on assets. First, the current work starts with the sample of non-financial firms obliged to present an Annual Corporate Governance Report to the Spanish Securities Market Commission with data from 2004. Second, the sample is reduced; excluding the companies not listed in the continuous market. The results indicate that only one company contributed to change the return on assets and becomes a model to study. One characteristic of this entity is their juridical form, as a cooperative.
Keywords: Gender; corporate governance; social economy; parity; director.